2007
DOI: 10.1111/j.1469-8129.2007.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Indifference towards national identity: what young adults think about being English and British*

Abstract: ABSTRACT. National identity should be sharply distinguished from nationalism. People speak by reference to a general and assumed membership of a country, and routine markers of behaviour and style may exhibit this sense of membership. This matter‐of‐fact acceptance of ‘national’ membership does not guarantee enthusiasm for the ‘nation’ and it cannot be taken as a signal of nationalism, banal or otherwise. While theoretical statements and assumptions often suggest that national identity is fundamental to indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 31 publications
4
72
1
Order By: Relevance
“…Category-ascription was treated as delicate here in that category-related feelings were rejected as implicating prejudiced or discriminatory views concerning other categories' members. Condor similarly concluded that expressions of English national identity can become a 'normatively accountable matter-of-prejudice' (Condor, 2000:181;Abell, 2011, andFenton, 2007, make similar points).…”
Section: Discussionmentioning
confidence: 99%
“…Category-ascription was treated as delicate here in that category-related feelings were rejected as implicating prejudiced or discriminatory views concerning other categories' members. Condor similarly concluded that expressions of English national identity can become a 'normatively accountable matter-of-prejudice' (Condor, 2000:181;Abell, 2011, andFenton, 2007, make similar points).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived threats including changes in the global marketplace AUTHOR COPY (Tsai, Lee, & Song, 2013), economic hardship (Balabanis, Diamantopoulos, Mueller, & Melewar, 2001) and terrorist activity (Coryn, Beale, & Myers, 2004;McFarland, 2005) have all been found to impact on levels of national pride. In a UK context, Fenton (2007) observed that feelings of 'Englishness' (and subsequent use of the St. George's Cross as opposed to the Union Jack) was in some part a response to the growing identities of Scotland and Wales respectively (hence described as a form of 'me-too-ism').…”
Section: National Identitymentioning
confidence: 99%
“…Individuals with strong nationalist views "tend to possess an unambiguously hostile conflict schema that predisposes them to an aggressive approach to inter-national conflict" (Federico et al, 2005, p. 624). It is perhaps a result of the fact that nationalism is associated with hooliganism, xenophobia and far-right political leanings (Abell, 2011) that English people either approach the notion of national identity with trepidation for fear of accusations of ethnocentrism (Condor, 2000) or even reject notions of national identity because of the behaviour of fellow nationals (Fenton, 2007).…”
Section: Nationalismmentioning
confidence: 99%
“…The different measures do not converge. Thin identities can be held with great intensity while thick identities may be unmarked in the everyday run of life: Englishness is a thick, highly institutionalised identity but is not normally highlighted, indeed researchers have found respondents avoiding the category (Condor, 2000 ;Edensor, 2002 ;Fenton, 2007 ). We need to allow for much finer shading and more varied combinations.…”
Section: Ethnicity and Religion: Redefining The Research Agenda Josepmentioning
confidence: 99%